(untitled) (World Bulletin of Education and Learning, 2026)
This scholarly article is devoted to the analysis of the life and role in state governance of Gawharshad Begim, one of the most influential figures of the Timurid Empire, the daughter-in-law of Amir Temur and the wife of Shahrukh Mirza. The paper examines the queen’s influence on political decision-making, her role in ensuring the stability of the state, and her significant contribution to the architectural and cultural development of her time. In addition, based on historical sources, the study substantiates with factual evidence Gawharshad Begim’s position as a central figure among political groups, her role in the upbringing of her sons, and the tragic circumstances of her death.